Local Wisdom Based Water Resources Conservation for Environmental Sustainability - Dharma Ferry (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2019)
The purpose of this research is about to find out how the society’s local wisdom of Lempur, Gunung Raya sub-district conserve water resources. Data and information were taken from interview and observation of river condition by observing its pH and transparency. This research adopts descriptive qualitative approach. The informants of this research were the leaders of custom Lekok Lima Puluh Tumbi Lempur and Village government of Lempur. The data were collected by taking the sample of river water quality, interview, and documentation. The data were analyzed by using interactive model concept proposed by Miles and Huberman (reduction, display, and verification). In general, the results of this research showed that local wisdom such as the customary law have not been implemented well yet. Based on the test of pollution parameter, it was found that the condition of waters did not achieve the level of danger yet because the level of pH is 7. It is expected that the society keep local wisdom in conserving water resources to make those water resources conserved well.